TIRZEPATIDE AND RETATRUTIDE IN THE TREATMENT OF OBESITY AND TYPE 2 DIABETES MELLITUS: CURRENT EVIDENCE AND FUTURE DIRECTIONS. A SYSTEMATIC REVIEW OF CURRENT LITERATURE - Rafał Bednarczyk,; Natalia Bednarczyk,; Radosław Krzysztof Binkowski,; Agnieszka Kurek,; Natalia Krajewska,; Aleksandra Lejman,; Aleksandra Mazurkiewicz,; Hubert Sidor,; Monika Wołosik,; Szymon Zysiak, (International Journal of Innovative Technologies in Social Science, 2026)
Background: The global prevalence of obesity and type 2 diabetes mellitus (T2DM) has achieved unprecedented levels, imposing substantial burdens on healthcare systems worldwide. Incretin-based pharmacotherapies have fundamentally transformed therapeutic approaches to these metabolic disorders over the past decade. Tirzepatide is a dual GIP/GLP-1 receptor agonist. Retatrutide additionally targets glucagon receptors. Both agents represent groundbreaking advances in metabolic pharmacotherapy.Objective: This comprehensive review synthesizes clinical evidence from trials conducted between 2014 and 2024, examining pharmacological mechanisms, therapeutic efficacy, safety characteristics, and prospective clinical applications of these novel multi-receptor agonists.Methods: We performed systematic literature searches across PubMed, Cochrane Library, Web of Science, and ClinicalTrials.gov databases. Selection criteria encompassed randomized controlled trials, systematic reviews, meta-analyses, and prospective cohort studies, adhering to PRISMA methodology throughout.Results: Phase 3 clinical trials showed superior efficacy of tirzepatide compared to existing pharmacotherapies, reaching body weight reductions of approximately 22.5% and hemoglobin A1c (HbA1c) reductions of up to 2.4 percentage points. Phase 2 trials of retatrutide revealed even more remarkable outcomes, with weight reductions approaching 24.2% over 48 weeks. Both medications exhibited favorable cardiovascular profiles, though gastrointestinal adverse events constitute the predominant tolerability concern.Conclusions: These pharmacological agents represent paradigm-shifting developments in obesity and diabetes management. Their therapeutic effectiveness approximates outcomes previously achievable only through surgical intervention, marking a transformative milestone for pharmacotherapy. Ongoing phase 3 trials will further elucidate their optimal positioning within clinical treatment algorithms.